Plasma surface treatment of transparent commercial polymers to improve their wettability, gas barrier, and optical transmittance in the visible range - Sant’Ana, Péricles Lopes [UNESP] (2022)
The objective of this work was to study the modification of the structural, chemical, and optical properties of the surface of certain commercial polymers through the use of Plasma Immersion and Plasma Immersion Ion Implantation techniques. The polymers investigated were blue polyvinyl chloride, polyethylene terephthalate, and low density polyethylene. As the fluorination of a surface tends to increase its hydrophobic character, sulfur hexafluoride plasmas were used as a fluorine source. Treatments with nitrogen plasmas were also investigated. Graphical abstract: An investigation at Nanoscale of a solid using Microscopy and spectroscopy methods are the key to the Nanoscience today, and the characterized materials may find several applications.